16.2: Invited Paper: Challenges and solutions for High‐performance GaN MicroLED displays. (4th October 2019) - Templier, F.; Bernard, J.; Caplet, S.; Bédoin, A.; Haas, Helge
Abstract : We discuss the main challenges for the fabrication of emerging microLED displays. We shown that microtube technology is very well adapted to these new kind of displays, since it provides both mechanical and electrical connection of the microLEDs on the receiving substrate. Also, we present a new fabrication approach, where an elementary unit consists of all‐in‐one‐ RBG MicroLEDs on CMOS driving circuit.